2019
DOI: 10.3390/sym11030429
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Analytical Solution for the Eigenvalue Problem of FGM Porous Circular Plates

Abstract: Free vibration analysis of the porous functionally graded circular plates has been presented on the basis of classical plate theory. The three defined coupled equations of motion of the porous functionally graded circular/annular plate were decoupled to one differential equation of free transverse vibrations of plate. The one universal general solution was obtained as a linear combination of the multiparametric special functions for the functionally graded circular and annular plates with even and uneven poros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The mesh displacement is maximum for the sonic excitation frequency of 75 Hz corresponding to the natural frequency of the speaker diaphragm. The maximum vertical displacement of the vibrating mesh screen can also be predicted from the porous circular plate approach in which the droplet weight opposes the sound pressure force acting normal to the mesh surface 29 ; hence resulting in the expression: , here: is sound pressure level, is the effective stiffness of mesh screen, is the droplet weight, is wire diameter, is Poison ratio, is the radius of the top speaker opening and is the elastic modulus of steel. The vertical displacement amplitude is predicted using the expression for the various mesh/plate structures considered in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The mesh displacement is maximum for the sonic excitation frequency of 75 Hz corresponding to the natural frequency of the speaker diaphragm. The maximum vertical displacement of the vibrating mesh screen can also be predicted from the porous circular plate approach in which the droplet weight opposes the sound pressure force acting normal to the mesh surface 29 ; hence resulting in the expression: , here: is sound pressure level, is the effective stiffness of mesh screen, is the droplet weight, is wire diameter, is Poison ratio, is the radius of the top speaker opening and is the elastic modulus of steel. The vertical displacement amplitude is predicted using the expression for the various mesh/plate structures considered in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Solving the simultaneous equation [Eqs. (20) and (21)] to find the unknowns and substitute back to Eq. (17).…”
Section: Application Of Galerkin Methods Of Weighted Residual To the Governing Equationmentioning
confidence: 99%
“…Meanwhile, the HPM also suffers the setback of finding the embedded parameter and initial approximation of the governing equation that satisfies the given conditions. Nonetheless, several researches on a free vibration of circular plates using different methods have been presented in the literature [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Moreover, the reliability and flexibility of the Galerkin method of weighted residual [26] have made it more effective than any other semi-numerical method.…”
Section: Introductionmentioning
confidence: 99%
“…The statistics of papers called for this Special Issue related to published or rejected items were [7][8][9][10][11][12][13][14][15][16][17][18][19][20]: total submissions (21), published (13; 62%), and rejected (8; 38%). The authors' geographical distribution by countries of authors in published papers is shown in Table 1, and it can be seen that 35 authors are from 11 different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%